THE PHENOMENON OF LAND-USE CHANGE AND THE APPLICATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) BY SUPPLEMENTARY ACCOMMODATIONS IN NORTH KUTA REGENCY, BALI, INDONESIA - Komang Ratih Tunjungsari; A.A. Ayu Arun Suwi Arianty (Journal of Business on Hospitality and Tourism, 2016)
The phenomenon in North Kuta is the tourist accomodations such as restaurants, villas, and housing residents, furthermore said with supplementary accomodations, are increasingly growing in number. This issue of tourism development and land-use change brought some impacts, especially in the environmental, social and economical issue. This research will discuss about the CSR concept in order to balance the effect of the land -use change especially in social and economic issues. The aim of this research is to discover the phenomenon of land use change in North Kuta regency and the application of CSR in developing and supporting local community. We use observation, questionnaires, and interview to data collection instruments or research instruments. Based on our research, we found that, the supplementary accommodations and restaurants in North Kuta regency are applied the CSR’s programs, still they do not provide structured CSR programs as the hotels provide.